First results from the Cornell high Q cw full linac cryo- module. Issue 1 (November 2015) - Eichhorn, R; Furuta, F; He, Y; Ge, M; Hoffstaetter, G; O'Connell, T; Quigley, P; Sabol, D; Sears, J; Smith, E; Liepe, M; Markham, S; et al.
Abstract: Cornell University has finished building a 10 m long superconducting accelerator module as a prototype of the main linac of a proposed ERL facility. This module houses 6 superconducting cavities- operated at 1.8 K in continuous wave (CW) mode - with individual HOM absorbers and one magnet/ BPM section. In pushing the limits, a high quality factor of the cavities (210 10 ) and high beam currents (100 mA accelerated plus 100 mA decelerated) were targeted. The design of the cryomodule and the results of components tested before assembly will be presented in this paper.